A Randomized Controlled Trial in a 14-Month Longitudinal Design to Analyze the Effects of a Peer Support Instant Messaging Service Intervention to Improve Diabetes Self-Management and Support - Elisabeth Höld; Ursula Hemetek; Katharina Tremmel; Tatjana Aubram; Johanna Grüblbauer; Martin Wiesholzer; Manuel Schwanda; Stefan Stieger (Diabetology)
Background/Objectives: The outcomes of diabetes therapy depend largely on how well patients can implement medical advice in their lives. The main aim of the DiabPeerS study was to evaluate a peer support instant messaging service (IMS) approach to diabetes self-management education and support (DSMES) for people with type 2 diabetes mellitus (T2DM). Methods: Participants with T2DM took part in a randomized controlled trial. Both the intervention group (IG) and the control group (CG) received standard therapy, but the IG additionally participated in the peer support IMS intervention. The duration of the intervention was 7 months, succeeded by a follow-up 7 months later. Eleven biochemical, six behavioral, and six psychosocial parameters were measured at four times. Results: The targeted sample size could not be reached, and 68 participants took part. The following results have been found for the main hypotheses: No influence on HbA1c was detected (IG: −0.27, CG: +0.06, p > 0.05). Diabetes self-management behaviors were unaffected (IGdiet: +0.02, CGdiet: +0.46, p > 0.05; IGexercise: −0.72, CGexercise: +0.44, p > 0.05; IGbloodsugar: −0.21, CGbloodsugar: +0.65, p > 0.05; IGfootcare: +0.37, CGfootcare: +1.13, p > 0.05). Quality of life increased during the intervention in both the IG (KSK: +8.92, PSK: +7.41, p < 0.001) and the CG (KSK: +8.73, PSK: +7.48, p < 0.001). Medication adherence increased in the IG (+3.31, p < 0.01), although these participants were still classified as non-adherent. Conclusions: A peer support IMS intervention is a promising approach, but we recommend combining the online setting with an initial face-to-face situation.